2019
DOI: 10.3389/fevo.2019.00157
|View full text |Cite
|
Sign up to set email alerts
|

High Wolbachia Strain Diversity in a Clade of Dung Beetles Endemic to Madagascar

Abstract: Determining the drivers of diversity is a major topic in biology. Due to its high level of micro-endemism in many taxa, Madagascar has been described as one of Earth's biodiversity hotspot. The exceptional Malagasy biodiversity has been shown to be the result of various eco-evolutionary mechanisms that have taken place on this large island since its isolation from other landmasses. Extensive phylogenetic analyses have, for example, revealed that most of the dung beetle radiation events have arisen due to allop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…The high level of endemism of Malagasy dung beetles and the diversity within the endemic lineages (Miraldo et al, 2011) also makes them ideal for studying factors affecting speciation. The evolutionary history of these groups has been established on a large scale, but the precise factors causing speciation need to be further studied (Miraldo & Duplouy, 2019;Wirta et al, 2008Wirta et al, , 2010. These factors include feeding patterns which play a strong role in dung beetle evolution (Davis, Scholtz, & Sole, 2016;Raine & Slade, 2019).…”
Section: Future Directions For Dung Beetle Research In Madagascarmentioning
confidence: 99%
“…The high level of endemism of Malagasy dung beetles and the diversity within the endemic lineages (Miraldo et al, 2011) also makes them ideal for studying factors affecting speciation. The evolutionary history of these groups has been established on a large scale, but the precise factors causing speciation need to be further studied (Miraldo & Duplouy, 2019;Wirta et al, 2008Wirta et al, , 2010. These factors include feeding patterns which play a strong role in dung beetle evolution (Davis, Scholtz, & Sole, 2016;Raine & Slade, 2019).…”
Section: Future Directions For Dung Beetle Research In Madagascarmentioning
confidence: 99%
“…Many of the records from this database were from specimens of the same species and the same population, we thus randomly deleted some of the duplicates to keep a maximum of three of each type. Additionally, we included all wsp, and MLSTs sequences from Wolbachia strains previously characterized from Bicyclus species [36](GenBank IDs: KY658538-52, KY658652, KY658655, and KY658572-90), and those from Malagasy dung beetles [9] (GenBank IDs: MK636654-66), that are not present in the PubMLST-Wolbachia database. The full list of specimens and sequences included in this study can be retrieved from Zenodo (doi:…”
Section: Habitats and Ecoregionsmentioning
confidence: 99%
“…These patterns thus suggest that Wolbachia may have jump jumped horizontally between host species throughout the ~ 400 million years of the symbiont evolutionary history [3,[5][6][7][8]. Hybridization events, followed by introgression between closely related species have been shown to support the interspecies transfer of various genetic entities, including Wolbachia [9][10][11]. Although recent common ancestry is an obvious reason to why two species can carry the same symbionts, studies have shown that it is not the only one (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…duplicates to keep a maximum of three of each type. Additionally, we included all wsp and MLSTs sequences from Wolbachia strains previously characterized from Bicyclus species [39](GenBank IDs: KY658538-52, KY658652, KY658655, and KY658572-90), and those from Malagasy dung beetles [11] (GenBank IDs: MK636654-66), that are not present in the PubMLST-Wolbachia database. The full list of specimens and sequences included in this study can be retrieved from Zenodo (doi:…”
mentioning
confidence: 99%